A review on shape memory alloys with applications to morphing aircraft - Barbarino, S; Saavedra Flores, E I; Ajaj, R M; Dayyani, I; Friswell, M I (Smart materials and structures, 2014)
Shape memory alloys (SMAs) are a unique class of metallic materials with the ability to recover their original shape at certain characteristic temperatures (shape memory effect), even under high applied loads and large inelastic deformations, or to undergo large strains without plastic deformation or failure (super-elasticity). In this review, we describe the main features of SMAs, their constitutive models and their properties. We also review the fatigue behavior of SMAs and some methods adopted to remove or reduce its undesirable effects. SMAs have been used in a wide variety of applications in different fields. In this review, we focus on the use of shape memory alloys in the context of morphing aircraft, with particular emphasis on variable twist and camber, and also on actuation bandwidth and reduction of power consumption. These applications prove particularly challenging because novel configurations are adopted to maximize integration and effectiveness of SMAs, which play the role of an actuator (using the shape memory effect), often combined with structural, load-carrying capabilities. Iterative and multi-disciplinary modeling is therefore necessary due to the fluid-structure interaction combined with the nonlinear behavior of SMAs.